2007
DOI: 10.1007/s11274-007-9364-0
|View full text |Cite
|
Sign up to set email alerts
|

Yield, size, and mushroom solids content of Agaricus bisporus produced on non-composted substrate and spent mushroom compost

Abstract: Three crops of Agaricus bisporus were grown on non-composted substrate (NCS), spent mushroom compost (SMC), a 50/50 mixture of NSC/SMC, or pasteurized Phase II compost. NCS consisted of oak sawdust (28% oven dry wt), millet (29%), rye (8%), peat (8%), ground alfalfa (4%), ground soybean (4%), wheat bran (9%) and CaCO 3 (10%). Substrates were nonsupplemented or supplemented with Target Ò (a commercial delayed release nutrient for mushroom culture) or soybean meal at spawning or casing, or with Micromax Ò (a mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…These substrate mixtures of NCS and SMS produced mushroom yields comparable to standard non-supplemented phase I compost [34,62]. A mushroom yield of 27.2 kg m 2 was obtained with a 50/50 mixture of NCS and SMS supplemented with 10% (dry wt) of a commercial delayed release nutrient at casing [33,34]. Moisture content of substrates significantly influenced mushroom yield [63].…”
Section: Sms Of Agaricus Sppmentioning
confidence: 99%
“…These substrate mixtures of NCS and SMS produced mushroom yields comparable to standard non-supplemented phase I compost [34,62]. A mushroom yield of 27.2 kg m 2 was obtained with a 50/50 mixture of NCS and SMS supplemented with 10% (dry wt) of a commercial delayed release nutrient at casing [33,34]. Moisture content of substrates significantly influenced mushroom yield [63].…”
Section: Sms Of Agaricus Sppmentioning
confidence: 99%
“…In this research, the highest yield was observed for a millet/5% soybean substrate with an additional amendment of 5% delayed-release supplement which produced 21.3 kg/m 2 with a BE of 273%. Mamiro et al (2007) and Mamiro and Royse (2008) grown A. bisporus on noncomposted substrate containing ground soybean (4%), spent mushroom compost, and mixtures of them, non-supplemented or supplemented with different nutrients, obtaining yields comparable to non-supplemented Phase II compost. Results confirm the possibility of producing mushrooms on non-composted substrates.…”
Section: Use For New Cultivation Substratesmentioning
confidence: 99%
“…Mamiro et al (2007) studied the use of the spent compost, mixtures of spent compost with noncomposted substrate and the supplementation period of the compost in the cultivation of A. bisporus and obtained the lowest indexes of productivity (4.9 kg/m 2 ) and biological efficiency (25.7%), by using spent compost without compost supplementation and the highest indexes of productivity (27.2 kg/m 2 ) and biological efficiency (144.3%) were reached when a 50/50 mixture of spent compost with non-composted substrate was used and the Target® (commercial nutrient for mushrooms) supplement was added at the moment of laying the cover of the compost.…”
Section: Resultsmentioning
confidence: 99%